2015
DOI: 10.1039/c5cp00246j
|View full text |Cite
|
Sign up to set email alerts
|

Improved sensitization efficiency in Er3+ ions and SnO2 nanocrystals co-doped silica thin films

Abstract: Er(3+) ions and SnO2 nanocrystals co-doped silica thin films are prepared by an improved sol-gel spin-coating method. With increase in annealing temperature, the related 1.54 μm characteristic emission intensity from Er(3+) ions is obviously enhanced by more than two orders of magnitude via SnO2 nanocrystals size control to boost the sensitization efficiency. Quantitative studies of steady-state spectroscopic data and fluorescence decay curves demonstrate that the related sensitization efficiency via size-tuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…where ε is the dielectric constant, m * is the effective mass, h c is the Planck constant, and the Bohr radius a Bohr =52.9 Å. For SnO 2 nanobelts, ε=13.5ε o [28,31], m * =0.35m o [32] and r Bohr =2.4 nm from equation (7). The Mott critical density is N C =2.8×10 19 cm −3 from equation (8).…”
Section: Mit Analysismentioning
confidence: 99%
“…where ε is the dielectric constant, m * is the effective mass, h c is the Planck constant, and the Bohr radius a Bohr =52.9 Å. For SnO 2 nanobelts, ε=13.5ε o [28,31], m * =0.35m o [32] and r Bohr =2.4 nm from equation (7). The Mott critical density is N C =2.8×10 19 cm −3 from equation (8).…”
Section: Mit Analysismentioning
confidence: 99%
“…Another effective way to enhance the emission efficiency of Er 3+ ions is co-doping with wider band gap semiconductors such as In 2 O 3 or SnO 2 NCs, which could transfer absorbed energy to nearby Er 3+ ions and suppress back energy transfer process [14][15][16][17]. In our previous work, the NIR photoluminescence (PL) intensity of Er 3+ ions was improved about 100-fold by co-doping In 2 O 3 NCs as sensitizer [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that nanoparticles of SnO 2 can effectively sensitize the emission of some RE ions [11] . Zhang X et al proposed that the effective sensitization process can be realized because of the suitable spectral overlap between the defect state energy level of SnO 2 nanoparticles and the excitation level of RE ions [12] .…”
Section: Introductionmentioning
confidence: 99%